Inquiry of the electron density transfers in chemical reactions: a complete reaction path for the denitrogenation process of 2, 3-diazabicyclo[2.2.1]hept-2-ene derivatives. Issue 48 (20th November 2015) - Safont, Vicent S.; González-Navarrete, Patricio; Oliva, Mónica; Andrés, Juan
Abstract : Unprecedented insight into the mapping of the electrons making/breaking the bonds in the DBH and DBOH denitrogenation processes. Abstract : A detailed study on all stages associated with the reaction mechanisms for the denitrogenation of 2, 3-diazabicyclo[2.2.1]hept-2-ene derivatives (DBX, with X substituents at the methano-bridge carbon atom, X = H and OH) is presented. In particular, we have characterized the processes leading to cycloalkene derivatives through migration-type mechanisms as well as the processes leading to cyclopentil-1, 3-diradical species along concerted or stepwise pathways. The reaction mechanisms have been further analysed within the bonding evolution theory framework at B3LYP and M05-2X/6-311+G(2d, p) levels of theory. Analysis of the results allows us to obtain the intimate electronic mechanism for the studied processes, providing a new topological picture of processes underlying the correlation between the experimental measurements obtained by few-optical-cycle visible pulse radiation and the quantum topological analysis of the electron localization function (ELF) in terms of breaking/forming processes along this chemical rearrangement. The evolution of the population of the disynaptic basin V(N1, N2) can be related to the experimental observation associated with the NN stretching mode evolution, relative to the N2 release, along the reaction process. This result allows us to determine why the N2 release is easier for the DBH case via a concerted mechanism compared to the stepwise mechanism found in the DBOH system. This holds the key to unprecedented insight into the mapping of the electrons making/breaking the bonds while the bonds change.